2002
DOI: 10.1637/0005-2086(2002)046[0525:rtvndv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Velogenic Newcastle Disease Virus in Leghorn Chickens by Use of Prophylactic Lymphokines

Abstract: A group of 1-day-old commercial leghorn chickens was prophylactically treated with lymphokines obtained from lymphocyte cultures of chickens previously infected with Salmonella enteritidis (S. enteritidis-immune lymphokines [SE-ILK]) with the objective to investigate the effect of SE-ILK on development of Newcastle disease (ND) infection caused by Chimalguacan strain, a Mexican velogenic ND virus (vNDV). Clinical signs, histologic lesions, and hemagglutination-inhibition (HI) serum titers were compared with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of the present study showed a significant increase in the Abs against ND in G3 compared with other groups, this return to the role of SILK enhancing the immune response after vaccination with live vaccines through drinking water in the first periods of chick life, also increasing response after oil vaccination these results agree with (15), whom demonstrated the role of SILK in increasing the cytokines which are natural stimulators and mediators of immune cells towards infectious organism thus increasing special Abs against antigens (Ag) and have an effective and influential role in stimulating and differentiation of immune cells in natural and acquired immunity. Rashad and Mushtaq,(10), demonstrated the role of SILK in protection the chicks from ND infection after challenge with virulent local isolate of ND in the first day.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study showed a significant increase in the Abs against ND in G3 compared with other groups, this return to the role of SILK enhancing the immune response after vaccination with live vaccines through drinking water in the first periods of chick life, also increasing response after oil vaccination these results agree with (15), whom demonstrated the role of SILK in increasing the cytokines which are natural stimulators and mediators of immune cells towards infectious organism thus increasing special Abs against antigens (Ag) and have an effective and influential role in stimulating and differentiation of immune cells in natural and acquired immunity. Rashad and Mushtaq,(10), demonstrated the role of SILK in protection the chicks from ND infection after challenge with virulent local isolate of ND in the first day.…”
Section: Discussionsupporting
confidence: 90%
“…In current intensive poultry production systems, chickens are exposed to a variety of potentially pathogenic microorganisms. Because of this huge antigenic exposure, vaccinations and/or antibiotic treatments are not always effective (Alfaro et al ., 2002). Genetic selection seems to be a promising alternative approach for improving disease resistance of birds (Gavora & Spencer, 1983; Lamont, 1998).…”
Section: Introductionmentioning
confidence: 99%